Spina bifida oculta in skeletal population from Dąbrówki (Poland, Podlaskie Province) - Myszka, Anna; Wolski, Adrian; Wawrzeniuk, Joanna; Tomczyk, Jacek (Anthropological Review, 2023)
The aim of the study is to evaluate the frequency of spina bifida oculta (SBO) in the early modern population from Dąbrówki (Poland); 26 males, 19 females, 3 adults with unspecified sex, 2 subadult were taken into the analysis. SBO was found in 9 individuals (18%), of whom only one exhibited a complete cleft in the sacrum (2%). In males, SBO was reported in 7 out of 26 skeletons studied (27%). Complete cleft was observed in one individual (4%), partial cleft in 6 individuals (23%). In females, no case of complete cleft was detected (0%), and one case of partial cleft was found (5%). These differences between males and females in the frequency of this skeletal condition were statistically significant. Due to the lack of uniform methods for SBO analyses, the inability to make interpopulation compari-sons, the relatively high prevalence of the SBO phenomenon in ancient and modern populations, and the unclear etiology of the disease, research on SBO should be continued.